Growth Status and Serum Zinc Level in Patients with Haemoglobin E-? Thalassemia (Bangladesh Journal of Child Health, 2012)
Background: Hb- E - ? thalassemia is a major congenital hematological disease of Bangladesh. These patients have poor growth and delayed maturation mainly due to iron overload but zinc deficiency also has been suggested as a contributing factor. Objectives: To investigate and compare the serum zinc of Hb E ? thalassemia patients and normal children and to see the relationship between serum zinc and growth status. Methods: This cross sectional study on Hb E ? thalassemia was under taken in the out patient department of Paediatric Haematology and Oncology department of Bangabandhu Sheikh Mujib Medical University from July 2009- May 2010. Total 31 children with Hb- E- ? thalassemia were enrolled for this study and matched 30 healthy children were taken as control. History of the cases were taken thoroughly and examination were done by the investigator himself. Anthropometry were measured properly and plotted in Centre for Disease Control (CDC) chart. Three ml (3 ml) of venous blood samples were drawn from both patient and control. Later on the blood samples were centrifuged and serum was stored at 20c till analysis for serum sinc level. Serum level of zinc was measured by using Flame Atomic Absorption Spectrophotometry following standard proceduve. Results: Mean serum zinc level in thalassemic group and control group were 97.4?g/dl (SD-18.4) and 99.6?g/dl (SD-18.7) respectively. There was no significant difference between two groups (p=.47). Mean percent of 50th centile of weight achieved was 75.9% in cases and 81% in control. Similarly mean percent of 50th centile of height achieved was 89% in cases and 93% in control. There was significant difference in height for age between both the groups (p=.05). Conclusion: Serum zinc level did not significantly changed in thalassemic group and control group children. But there were significant stunting in Hb E ? thalassemia patients and no significant difference was found between these children in terms of weight for age. DOI: http://dx.doi.org/10.3329/bjch.v36i2.13083 Bangladesh J Child Health 2012; Vol 36 (2): 76-81